KERAGAMAN KLON PHALAENOPSIS HASIL RADIASI SINAR GAMMA : PERUBAHAN FENOTIF FASE PERTUMBUHAN VEGETATIF - Astutik Astutik (Universitas Tribhuwana Tunggadewi, 2012)
Phalaenopsis is the most popular orchid for the consumer, because it has unique and interesting color, shape and size of flower and some flowers fragrant. One of the ways to improve the diversity of color and shape of the Phalaenopsis flower can be done by artificial mutation through gamma radiation. The study aims to determine the effect of Gamma ray radiation in Phalaenopsis phenotypes during vegetative growth. The experiment was conducted in two places; the implementation of radiation was carried out in BATAN Jakarta and then acclimatized in Green’s house of farmers in Bumiayu Village, Kedung Kandang, Malang in the months from January to June 2011. The experiment was arrange single Completely Randomized Design using dosage of gamma radiation treatment five levels: 0 krad (R0); 1.0 krad (R1); 2.0 krad (R2); 3.0 krad (R3) and 4, 0 krad (R4). Each treatment consist of fivereplication. The observations were made on the parameters of the number of leaves and the length and width of leaves at week 4, 8, 12, 16, the percentage (%) of plant life, color and leaf shape and the content of chlorophyll were measured at the end of the observation. The results show that the dosage of Gamma radiation influenced the number in leaves, the leaves color and shape, the amount of chlorophyll, but has no effect on the length and width of leaves at 16 weeks after radiation. The higher dose of gamma rays affected the vegetative growth slowest at dosage of 4.0 krad. Gamma ray dosage from 1.0 to 4.0 krad are able to produce color change in Phalaenopsis leaves